A recommended practical approach to the management of anthracycline-based chemotherapy cardiotoxicity: an opinion paper of the working group on drug cardiotoxicity and cardioprotection, Italian Society of Cardiology. (May 2016) - Spallarossa, Paolo; Maurea, Nicola; Cadeddu, Christian; Madonna, Rosalinda; Mele, Donato; Monte, Ines; Novo, Giuseppina; Pagliaro, Pasquale; Pepe, Alessia; Tocchetti, Carlo G.; Zito, Concetta; Mercuro, Giuseppe
Abstract : Anthracyclines are the mainstay of treatment of a variety of haematological malignancies and solid tumours. Unfortunately, the clinical use of these drugs is limited by cumulative, dose-related cardiotoxicity which may ultimately lead to a severe and irreversible form of cardiomyopathy. Thus, there is an increasing need for close cooperation among cardiologists, oncologists and haemato-oncologists. As anthracyclines save lives, the logical goal of this cooperation, besides preventing or mitigating cardiotoxicity, is to promote an acceptable balance between the potential cardiac side effects and the vital benefit of anticancer treatment. This manuscript, which is specifically addressed to the cardiologist who has not accumulated much experience in the field of cancer therapy, focuses on several topics, that is old and new mechanisms of cardiac toxicity, late cardiac toxicity, the importance of overall risk assessment, the key role of a cardiology consult before starting cancer therapy, and the pros and cons of primary and secondary prevention programmes.